2021
DOI: 10.3390/polym13162690
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxyquinoline-5-Sulfonic Acid-Containing Poly(Vinyl Alcohol)/Chitosan Electrospun Materials and Their Cu2+ and Fe3+ Complexes: Preparation, Antibacterial, Antifungal and Antitumor Activities

Abstract: Novel poly(vinyl alcohol) (PVA)/chitosan (Ch)-based fibrous materials containing an ionizable model drug, 8-hydroxyquinoline-5-sulfonic acid (SQ), were successfully fabricated by electrospinning. Complexes between the components of the crosslinked PVA/Ch/SQ mats and Cu2+ and Fe3+ ions were formed. The coordination of these ions in the mats was examined by electron paramagnetic resonance spectroscopy (EPR). The microbiological screening against S. aureus and C. albicans revealed that both the incorporation of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…As previously highlighted, electrospun drug-loaded nanofibers offer high drug loading, exceptional encapsulation efficiency, and specific drug release profiles, including sustained, multiphase, targeted, and combined release. These capabilities are achieved through meticulous material selection and design, presenting specific and extensive applications in cancer treatment [ 113 , 114 , 115 ]. This section delineates their applications across various tumor therapies.…”
Section: Application Of Drug-loaded Nanofibers In Cancer Therapymentioning
confidence: 99%
“…As previously highlighted, electrospun drug-loaded nanofibers offer high drug loading, exceptional encapsulation efficiency, and specific drug release profiles, including sustained, multiphase, targeted, and combined release. These capabilities are achieved through meticulous material selection and design, presenting specific and extensive applications in cancer treatment [ 113 , 114 , 115 ]. This section delineates their applications across various tumor therapies.…”
Section: Application Of Drug-loaded Nanofibers In Cancer Therapymentioning
confidence: 99%
“…Chitosan [β-(1–4)-2-amino-2-deoxy- d -glucan], a cationic polymer derived from the deacetylation of chitin found in shrimp and crab shells, , exhibits potent antimicrobial, antioxidant, and antitumor properties and holds great potential for applications in biogenic pesticides, functional foods, and biomaterials. However, its large molecular weight creates limitations because it can only be dissolved at acidic pH, thereby creating challenges for its use . To overcome these limitations, researchers have synthesized chitosan oligosaccharide (COS) via chemical or enzymatic hydrolysis .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the metal ions could easily combine with oxygen in organisms, and then denatured proteins or enzymes [16,17] through effect on the synthesis of amino acids, proteins, lipoproteins and coenzymes according with the formation of stable complexes. The antibacterial activity of chitosan Schiff base metal complexes [Cu(II) [18,19], Ag (II) [20,21], Zn(II) [22]] against E. coli, S. aureus, salmonella and B. subtilis was signi cantly higher than that of free ligand, and increased with the increase of the minimum concentration [23,24]. A novel water-soluble isoniazid grafted O-carboxymethyl chitosan Schiff base [25] was synthesized by chitosan, 1,3-diphenyl-1, 3-propanedione and mono chloroacetic acid, and then its metal complexes [Co(II), Cu(II), Zn(II)] was obtained, moreover, the results of antibacterial activity tests showed that the metal complexes exhibited better inhibitory effect on P. aeruginosa and S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the metal ions could easily combine with oxygen in organisms, and then denatured proteins or enzymes [23,24] through effect on the synthesis of amino acids, proteins, lipoproteins, and coenzymes according with the formation of stable complexes. The antibacterial activity of chitosan Schiff base metal complexes [Cu(II), [25,26] Ag (II), [27,28] Zn(II) [29] ] against E. coli, S. aureus, salmonella, and B. subtilis was significantly higher than that of free ligand, and increased with the increase of the minimum concentration. [30,31] It only needs small concentration to achieve good antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%